Characterization of Scrape‐Off Layer Turbulence Changes Induced by a Non‐Axisymmetric Magnetic Perturbation in an ASDEX Upgrade Low Density L‐Mode. Issue 3 (April 2014) - Müller, H. W.; Carralero, D.; Birkenmeier, G.; Conway, G. D.; Fischer, R.; Happel, T.; Manz, P.; Suttrop, W.; Wolfrum, E.; ASDEX Upgrade Team,
Abstract In the tokamak ASDEX Upgrade the influence of a non‐axisymmetric n = 2 error field on the turbulence in the far scrape‐off layer of a low density L‐mode discharge has been studied. There is no density pump‐out with the non‐axisymmetric perturbation but an increase of the scrape‐off layer density at the outer midplane. While the relative ion saturation current fluctuation level in the far scrape‐off layer is decreasing, the skewness rises and especially the excess kurtosis grows by a factor of 1.5–3. The frequency of intermittent events (blobs) is increasing by 50 %. Also the poloidal velocity grows with the magnetic perturbation while the typical turbulent structure size becomes smaller by a factor 5–10 about 20–25 mm outside the separatrix. The local spectral density has been calculated from a two‐point measurement of the ion saturation current. It is used to derive a dispersion relation. Two poloidal propagation velocities depending on the wave number have been found. One is an upper limit for the bulk E × B velocity and the second one the lower limit of the phase velocity. There is a significant contribution of the phase velocity to the propagation speed in the far scrape‐off layer. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)